EFFECT OF LIQUID NITROGEN LEVELS DURING STORAGE ON QUALITY OF FROZEN SEMEN OF GIR BULLS - SONAR, B P; TIWARl, R P; MISHRA, G K; POYAM, M R; PANDEY, A K; NAIR, A K; SAHASRABUDDHE, S A (The Indian Journal of Animal Reproduction, 2023)
A total of 50 semen ejaculates collected from 5 Gir bulls were frozen and stored in 3 liter container to studythe effect of different levels of liquid nitrogen on various post thaw seminal attributes. Overall mean values of postthaw motility, hypo osmotic swelling reactive sperm and cervical mucus penetration were 54.33 ± 1.18, 52.33±1.37, 47.00 ± 1.18, 28.67 ± 1.14%, 55.73 ± 2.08, 53.93 ± 1.70, 48.93 ± 2.18, 38.07 ± 1.79%, and 29.13 ± 0.96,28.33 ± 0.83, 26.53 ± 1.06 and 19.87 ± 0. 72 mm while liquid nitrogen level was full, 314th, half and 114th of frozensemen straw, respectively. The overall percent post thaw motility, percent HOS positive sperm and the meandistance traveled by vanguard spermatozoa (CMPT) was found significantly lower (P
Keywords: CMPT; HOST; PTM; Seminal attributes; Gir bulls